Toward a New Algorithm for Nonlinear Fractional Differential Equations (Advances in Applied Mathematics and Mechanics, 2013)
This paper is concerned with the development of an efficientalgorithm for the analytic solutions of nonlinear fractionaldifferential equations. The proposed algorithm Laplace homotopyanalysis method (LHAM) is a combined form of the Laplace transformmethod with the homotopy analysis method. The biggest advantagethe LHAM has over the existing standard analytical techniques isthat it overcomes the difficulty arising in calculatingcomplicated terms. Moreover, the solution procedure is easier,more effective and straightforward. Numerical examples areexamined to demonstrate the accuracy and efficiency of theproposed algorithm.